2010
DOI: 10.1186/1471-213x-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of zebrafish cyclin G-associated kinase (GAK) function impairs the expression of Notch-dependent genes during neurogenesis and causes defects in neuronal development

Abstract: BackgroundThe J-domain-containing protein auxilin, a critical regulator in clathrin-mediated transport, has been implicated in Drosophila Notch signaling. To ask if this role of auxilin is conserved and whether auxilin has additional roles in development, we have investigated the functions of auxilin orthologs in zebrafish.ResultsLike mammals, zebrafish has two distinct auxilin-like molecules, auxilin and cyclin G-associated kinase (GAK), differing in their domain structures and expression patterns. Both zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
(76 reference statements)
0
12
1
Order By: Relevance
“…GWAS have identified an increasing number of candidate risk genes in PD, several of which have VDR-binding sites closely associated with them raising the possibility that vitamin D may influence their expression. The biological relevance of a subset of these susceptibility genes with associated VDR binding on brain function has been well delineated with evidence for roles in nigrostriatal dopaminergic neurotransmission, neurogenesis and neurite outgrowth, and neural ectodermal expression (especially within the marginal and subventricular zones) (see Table 2) [140][141][142][143][144]. (ii) Amyotrophic lateral sclerosis Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting both the central and peripheral nervous systems [145].…”
Section: B Neurological Diseasementioning
confidence: 99%
“…GWAS have identified an increasing number of candidate risk genes in PD, several of which have VDR-binding sites closely associated with them raising the possibility that vitamin D may influence their expression. The biological relevance of a subset of these susceptibility genes with associated VDR binding on brain function has been well delineated with evidence for roles in nigrostriatal dopaminergic neurotransmission, neurogenesis and neurite outgrowth, and neural ectodermal expression (especially within the marginal and subventricular zones) (see Table 2) [140][141][142][143][144]. (ii) Amyotrophic lateral sclerosis Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting both the central and peripheral nervous systems [145].…”
Section: B Neurological Diseasementioning
confidence: 99%
“…When morpholinos are used to excise a small region of the kinase domain of GAK in zebrafish, the brain has developmental defects due to impairment of notch signaling (Bai et al, 2010), just as observed in Drosophila (Eun et al, 2008;Hagedorn et al, 2006). Surprisingly, a similar phenotype in the zebrafish is obtained when morpholinos are used to generate a nonsense mutation in the PTEN-like domain of GAK (Bai et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…When morpholinos are used to excise a small region of the kinase domain of GAK in zebrafish, the brain has developmental defects due to impairment of notch signaling (Bai et al, 2010), just as observed in Drosophila (Eun et al, 2008;Hagedorn et al, 2006). Surprisingly, a similar phenotype in the zebrafish is obtained when morpholinos are used to generate a nonsense mutation in the PTEN-like domain of GAK (Bai et al, 2010). However, there has been no attempt to rescue the zebrafish defects with a fragment comprising just the clathrinbinding and J-domains of GAK so it is unclear whether, as in Drosophila (Eun et al, 2008;Kandachar et al, 2008), these domains are sufficient for GAK function in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAK knockdown by siRNA in HeLa cells resulted in increased activation of ERK1/2, ERK5, and AKT (38), whereas introduction of dominant-negative dynamin, another protein involved in receptor trafficking, inhibited MAPK activation (41). GAK depletion has been linked to decrease in expression of Her4, a Notch target gene, in zebrafish models (42). Two receptors (IGF-IR and EGFR) that have been repeatedly described in osteosarcoma were analyzed to assess the effect of GAK depletion on their expression.…”
Section: Discussionmentioning
confidence: 99%